College physics : Part 2 (Quezon City, Philippines : Filipino Educators, Inc., 1963)
This book on College physics is the first to be published by Filipino authors. The many years of teaching experience of the authors in the subject, coupled with the spirit to render service to our educational system, has been the irresistable factors that have induced the authors to write this volume on College Physics.
Chapter 22. Wave motion -- Chapter 23. Production and reception of sound -- Chapter 24. Magnetism -- Chapter 25. Electrostatics -- Chapter 26. Electric field -- Chapter 27. Electric current and electrical circuits -- Chapter 28. Electrochemical effects and thermoelectricity -- Chapter 29. Electromagnetism -- Chapter 30. Capacitor and capacitance -- Chapter 31. Induced electromotive force; electromagnetic induction -- Chapter 32. Alternating current -- Chapter 33. Electromagnetic waves electronics -- Chapter 34. Nature of light -- Chapter 35. Illumination; photometry -- Chapter 36. Reflection; Mirrors -- Chapter 37. Refraction -- Chapter 38. Lense: images formed by lenses -- Chapter 39. Optical instruments -- Chapter 40. Interference;difraction -- Chapter 41. Polarization -- Chapter 42. Relativity -- Chapter 43. Optical spectra and atomic structure -- Chapter 44. The nucleus; radioactivity.
Includes index.
Keywords: PHYSICS -- COLLEGE